2022
DOI: 10.3390/ijerph19127225
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Age of Male National Team of Ukraine in Kyokushin Karate—Pilot Study

Abstract: This article is a continuation of the research on personality in combat sports in karate. The authors’ goal was to verify the relationship between personality and age of kyokushin karate practitioners. The male national team of Ukraine in karate kyokushin (N = 7) participated in the personality study with the use of the Big Five model. The NEO-FFI (NEO Five-Factor Inventory) Personality Questionnaire was applied as a research tool and the package of statistical methods IBM SPSS Statistics 27.0 (IBM Polska, War… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The duration of practising martial arts and higher qualifications are associated with better skills and greater self-control, self-esteem, and social skills ( 20 , 38 ). As discussed earlier, this should provide protection against bullying.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The duration of practising martial arts and higher qualifications are associated with better skills and greater self-control, self-esteem, and social skills ( 20 , 38 ). As discussed earlier, this should provide protection against bullying.…”
Section: Discussionmentioning
confidence: 99%
“…The fight takes place in close contact and allows blows to be inflicted with full force. The fight takes place without any protection (except for the suspension and the protector; for women, the chest protector)” [( 38 ) p. 36]. Athletes' qualification is evaluated according to the rank system from 10 (orange belt, the lowest) to 1 (brown belt with black stripe) Kyu and from 1 (black belt with one gold stripe) to 10 Dan (black belt with ten gold stripes, the highest).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in Poland among athletes (n=1260) aged between 20 to 29 years showed that champions (n=118) scored very low in neuroticism trait, high on extraversion and Conscientiousness, and average in Agreeableness and Openness to experience (Piepiora & Piepiora, 2021) [16] . Piepiora et al (2022) [25] identify a relationship between the big five traits and sports experience in another study. They found a negative correlation between sports experience and neuroticism and a positive correlation between sports experience and the other four traits.…”
Section: Big Five Personality Traits and Sportsmentioning
confidence: 95%